Universal depression prevention: An umbrella review of meta-analyses. (December 2021) - Hoare, Erin; Collins, Sam; Marx, Wolfgang; Callaly, Edward; Moxham-Smith, Ryan; Cuijpers, Pim; Holte, Arne; Nierenberg, Andrew A.; Reavley, Nicola; Christensen, Helen; Reynolds, Charles F.; Carvalho, Andre F.; et al.
Abstract: Depression is a disabling, highly prevalent, frequently chronic, and difficult-to-treat disorder with an immense cognitive, social, and economic burden. Given that many of the advances in other non-communicable disorders like cancer have been in prevention rather than treatment, the prevention of depression is currently an unmet public health priority. We sought to provide an overview of the meta-analytic literature through conducting a systematic umbrella review of universally delivered preventive interventions for depression. The search was conducted on March 18, 2021 utilising the following databases (all accessed through EBSCOHost); Allied and Complementary Medicine Database, CINAHL Complete, Global Health, Health Source: Nursing/Academic Edition, MEDLINE Complete and APA PsychArticles. The following search terms related to depression, prevention, and trial study design. Two authors independently screened articles and a third resolved discrepancies. Eligibility criteria sought to identify meta-analyses that investigated the prevention of depression (i.e., reduced incidence) through intervention studies that were universal, in that they were designed to be delivered to entire populations Six meta-analyses on psychological interventions, two school-based meta-analyses, and one eHealth meta-analysis were included in this umbrella review. Findings indicated that all identified studies were of good quality and one was of fair quality. One previous meta-review that examined physical activity to prevent depression was included in results, comprising eight meta-analyses. Preventive interventions have primarily and successfully utilized psychological therapeutic components, delivered at the school, community, and workplace settings. Both school- and eHealth-based interventions hold some utility for depression prevention. There is meta-analytic evidence that physical activity is efficacious for depression prevention. However, universal prevention is inconsistently defined. There is a pressing need for well-designed randomized controlled preventative interventions for depression before recommendations can be universally accepted with convincing level of evidence.